A new strikingly coloured species of Siphonocryptus, sixth of its order (Diplopoda: Siphonocryptida) - Enghoff, Henrik (Zootaxa, 2010)
The small millipede family Siphonocryptidae was revised by Enghoff & Golovatch (1995) who assigned two genera and three species to it: Siphoncryptus compactus Pocock, 1894, from Sumatra, S. latior Enghoff & Golovatch, 1995, from the Malaccan peninsula, and Hirudicryptus canariensis (Loksa, 1967) from the Canary and Madeiran archipelagos in the Atlantic Ocean. This highly disjunct distribution pattern has later become partly filled out by Hirudicryptus taiwanensis Korsós et al., 2008, from Taiwan, and H. quintumelementum Korsós et al., 2009, from Nepal.